High prevalence of co-infection between human papillomavirus (HPV) 51 and 52 in Mexican population - Jazbet Gallegos-Bolaños; Jessica Alejandra Rivera-Domínguez; José Miguel Presno-Bernal; Rodolfo Daniel Cervantes-Villagrana (BMC Cancer, 2017)
Abstract Background Human papillomavirus (HPV) is associated with the genesis of cervical carcinoma. The co-infection among HPV genotypes is frequent, but the clinical significance is controversial; in Mexico, the prevalence and pattern of co-infection differ depending on the geographic area of study. We analyzed the mono- and co-infection prevalence of multiple HPV genotypes, as well as preferential interactions among them in a Mexico City sample population. Methods This study was designed as a retrospective cohort study. Cervical cytology samples from 1163 women and 166 urethral scraping samples of men were analyzed between 2010 and 2012. The detection of HPV infection was performed using the hybrid capture and the genotyping was by PCR (HPV 6, 11, 16, 18, 30, 31, 33, 35, 45, 51, and 52). Results 36% of women were HPV-positive and the most prevalent genotypes were HPV 51, 52, 16, and 33 (42, 38, 37, and 34%, respectively). The prevalence of co-infection was higher (75.37%) than mono-infection in women HPV positives. All genotypes were co-infected with HPV 16, but the co-infection with 51–52 genotypes was the most frequent combination in all cases. Conclusion The co-infection was very common; each HPV genotype showed different preferences for co-infection with other genotypes, HPV 51–52 co-infection was the most frequent. The HPV 16, 33, 51 and 52 were the most prevalent and are a public health concern to the Mexican population.